2021
DOI: 10.1186/s12987-021-00264-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased extracellular fluid is associated with white matter fiber degeneration in CADASIL: in vivo evidence from diffusion magnetic resonance imaging

Abstract: Background White matter hyperintensities (WMHs) are one of the hallmarks of cerebral small vessel disease (CSVD), but the pathological mechanisms underlying WMHs remain unclear. Recent studies suggest that extracellular fluid (ECF) is increased in brain regions with WMHs. It has been hypothesized that ECF accumulation may have detrimental effects on white matter microstructure. To test this hypothesis, we used cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
(59 reference statements)
0
18
0
1
Order By: Relevance
“…Zhang et al have reported that an increased pericarotid fat density is associated with the presence of lacunes, and may be linked to CSVD ( Zhang et al, 2021 ). A previous cross-sectional study has provided evidence which linked lacunes and WMHs to a common pathogenesis of CSVD ( Yu et al, 2021 ). In addition, CSVD subtype 2 and subtype 3 also showed higher possibility of PVWMH but not deep WMH (DWMH) compared with subtype 1.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al have reported that an increased pericarotid fat density is associated with the presence of lacunes, and may be linked to CSVD ( Zhang et al, 2021 ). A previous cross-sectional study has provided evidence which linked lacunes and WMHs to a common pathogenesis of CSVD ( Yu et al, 2021 ). In addition, CSVD subtype 2 and subtype 3 also showed higher possibility of PVWMH but not deep WMH (DWMH) compared with subtype 1.…”
Section: Discussionmentioning
confidence: 99%
“…Increased FW also correlated with an IL‐18–centered inflammatory network, 85 was found to mediate the association between deep medullary veins disruption and WM integrity in cSVD, 16 was related to geriatric depressive symptoms 86 and presented a stronger association with cognitive deficits than the conventional DTI method, showing it to be a marker of cSVD‐related degeneration 87 . Extracellular fluid quantified with FW‐related parameters associated positively with microstructural degeneration and the presence of lacunes and CMB in CADASIL patients, suggesting a role for extracellular fluid in cSVD pathology 88 …”
Section: Resultsmentioning
confidence: 95%
“…87 Extracellular fluid quantified with FW-related parameters associated positively with microstructural degeneration and the presence of lacunes and CMB in CADASIL patients, suggesting a role for extracellular fluid in cSVD pathology. 88 An alternative diffusion tensor decomposition model has been developed to provide isotropic and anisotropic tensor components. Such parameters were significantly correlated with executive functions, IPS, and conversion to dementia in a 3-year longitudinal study.…”
Section: Brain Structural Networkmentioning
confidence: 99%
“…The present study suggests that FW in the SWM may constitute an early marker of white matter microstructural abnormality in CSVD. Although FW was originally estimated to correct for freely diffusing extracellular water (Pasternak et al, 2009 ), many studies have found that FW is particularly sensitive to disease severity (Duering et al, 2018 ; Gullett et al, 2020 ; Huang, Zhang, Jiaerken, Wang, Hong, et al, 2021 ; Ji et al, 2017 ; Maillard et al, 2019 ; Yu et al, 2021 ). Using FW imaging, increasing evidence suggests a prominent increase in extracellular water in CSVD, with less demyelination and axonal loss than would be suggested by conventional diffusion measures (Duering et al, 2018 ; Wardlaw et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%